Implementasi Metode AHP dalam Penentuan Spesifikasi Pegawai SPG (Sales Promotion Girl) - Satria Satria; Lilin Hardiyani (Jurnal ICT : Information Communication & Technology, 2021)
PT Mitra Andal Sejati is a company engaged in promotional services and services. The services provided are brand activation activities and the management of SPG (Sales Promotion Girl). The biggest client who collaborates with PT Mitra Andal Sejati is PT Unilever Indonesi Tbk. PT Mitra Andal Sejati has a vision to prepare a sales promotion girl who is proactive to customers and able to provide knowledge to customers about the latest products. Currently in the recruitment of sales promotion girls, Unilever, the company does not have an objective standard of assessment. There are still many sales promotion girls who do not understand the content in the product so that they are unable to convey product advantages to customers, which results in a lack of product knowledge in customers and many SPGs are above the average age of an SPG. To help solve the problem of determining the need for SPG specifications because AHP uses multicriteria that are compared with alternatives, thereby reducing the subjectivity in determining the weight of the criteria. The result of the selection of applicants who were accepted to work as sales promotion girls was only 5 applicants with the highest score based on the recruitment results from 10 samples of applicants